Extensively Expanded Auricular Chondrocytes Form Neocartilage In Vivo. (October 2014) - Tseng, Alan; Pomerantseva, Irina; Cronce, Michael J.; Kimura, Anya M.; Neville, Craig M.; Randolph, Mark A.; Vacanti, Joseph P.; Sundback, Cathryn A.
Objective . Our goal was to engineer cartilage in vivo using auricular chondrocytes that underwent clinically relevant expansion and using methodologies that could be easily translated into health care practice. Design . Sheep and human chondrocytes were isolated from auricular cartilage biopsies and expanded in vitro . To reverse dedifferentiation, expanded cells were either mixed with cryopreserved P0 chondrocytes at the time of seeding onto porous collagen scaffolds or proliferated with basic fibroblast growth factor (bFGF). After 2-week in vitro incubation, seeded scaffolds were implanted subcutaneously in nude mice for 6 weeks. The neocartilage quality was evaluated histologically; DNA and glycosaminoglycans were quantified. Cell proliferation rates and collagen gene expression profiles were assessed. Results . Clinically sufficient over 500-fold chondrocyte expansion was achieved at passage 3 (P3); cell dedifferentiation was confirmed by the simultaneous COL1A1/3A1 gene upregulation and COL2A1 downregulation. The chondrogenic phenotype of sheep but not human P3 cells was rescued by addition of cryopreserved P0 chondrocytes. With bFGF supplementation, chondrocytes achieved clinically sufficient expansion at P2; COL2A1 expression was not rescued but COL1A1/3A1genes were downregulated. Although bFGF failed to rescue COL2A1 expression during chondrocyte expansion in vitro, elastic neocartilage with obvious collagen II expression was observed on porous collagen scaffolds after implantation in mice for 6 weeks. Conclusions . Both animal and human auricular chondrocytes expanded with low-concentration bFGF supplementation formed high-quality elastic neocartilage on porous collagen scaffolds in vivo .